Surveillance Imaging and Alpha Fetoprotein for Early Detection of Hepatocellular Carcinoma in Patients With Cirrhosis: A Meta-analysis - Tzartzeva, Kristina; Obi, Joseph; Rich, Nicole E; Parikh, Neehar D; Marrero, Jorge A; Yopp, Adam; Waljee, Akbar K; Singal, Amit G (Gastroenterology (New York, N.Y. 1943), 2018)
Society guidelines differ in their recommendations for surveillance to detect early-stage hepatocellular carcinoma (HCC) in patients with cirrhosis. We compared the performance of surveillance imaging, with or without alpha fetoprotein (AFP), for early detection of HCC in patients with cirrhosis. Two reviewers searched MEDLINE and SCOPUS from January 1990 through August 2016 to identify published sensitivity and specificity of surveillance strategies for overall and early detection of HCC. Pooled estimates were calculated and compared using the DerSimonian and Laird method for a random effects model. The study was conducted in accordance with Preferred Reporting Items for Systematic Review and Meta-analysis guidelines. Thirty-two studies (comprising 13,367 patients) characterized sensitivity of imaging with or without AFP measurement for detection of HCC in patients with cirrhosis. Ultrasound detected any stage HCC with 84% sensitivity (95% confidence interval [CI] 76%-92%), but early-stage HCC with only 47% sensitivity (95% CI 33%-61%). In studies comparing ultrasound with vs without AFP measurement, ultrasound detected any stage HCC with a lower level of sensitivity than ultrasound plus AFP measurement (relative risk [RR] 0.88; 95% CI 0.83-0.93) and early-stage HCC with a lower level of sensitivity than ultrasound plus AFP measurement (RR 0.81; 95% CI 0.71-0.93). However, ultrasound alone detected HCC with a higher level of specificity than ultrasound plus AFP measurement (RR 1.08; 95% CI 1.05-1.09). Ultrasound with vs without AFP detected early-stage HCC with 63% sensitivity (95% CI 48%-75%) and 45% sensitivity (95% CI 30%-62%), respectively (P = .002). Only 4 studies evaluated computed tomography or magnetic resonance image-based surveillance, which detected HCC with 84% sensitivity (95% CI 70%-92%). We found ultrasound alone has a low sensitivity to detect early stage HCC in patients with cirrhosis. Addition of AFP to ultrasound significantly increases sensitivity of early HCC detection in clinical practice.